Geographical accessibility of emergency neonatal care services in Ethiopia: analysis using the 2016 Ethiopian Emergency Obstetric and Neonatal Care Survey. Issue 6 (9th June 2022) - Kibret, Getiye Dejenu; Demant, Daniel; Hayen, Andrew
Abstract : Introduction: Access to emergency neonatal health services has not been explored widely in the Ethiopian context. Accessibility to health services is a function of the distribution and location of services, including distance, travel time, cost and convenience. Measuring the physical accessibility of health services contributes to understanding the performance of health systems, thereby enabling evidence-based health planning and policies. The physical accessibility of Ethiopian health services, particularly emergency neonatal care (EmNeC) services, is unknown. Objective: To analyse the physical accessibility of EmNeC services at the national and subnational levels in Ethiopia. Methods: We analysed the physical accessibility of EmNeC services within 30, 60 and 120 min of travel time in Ethiopia at a national and subnational level. We used the 2016 Ethiopian Emergency Obstetric and Neonatal Care survey in addition to several geospatial data sources. Results: We estimated that 21.4%, 35.9% and 46.4% of live births in 2016 were within 30, 60 and 120 min of travel time of fully EmNeC services, but there was considerable variation across regions. Addis Ababa and the Hareri regional state had full access (100% coverage) to EmNeC services within 2 hours travel time, while the Afar (15.3%) and Somali (16.3%) regional states had the lowest access. Conclusions: The physical access to EmNeC services in Ethiopia is well below the universal health coverage expectations stated by the United Nations. Increasing the availability of EmNeC to health facilities where routine delivery services currently are taking place would significantly increase physical access. Our results reinforce the need to revise service allocations across administrative regions and consider improving disadvantaged areas in future health service planning.